The comparison of medial longitudinal arch development in normal feet and flexible flatfeet in preschool children with an 18-month follow-up: a retrospective case-control study. Issue 3 (May 2021) - Farahmand, Behshid; Pourhoseingholi, Ensieh; Bagheri, Azam
Abstract : Background: Flexible flatfoot is a major concern for parents of preschool children. Although the medial longitudinal arch (MLA) has significant development during the growth of a child, flexible flatfoot usually does not need treatment. However, the time and process of MLA changes are controversial among researchers. The aim of this study was to compare MLA development in preschool children with normal feet and with flexible flatfoot. Methods: Sixty preschool children (36 girls and 24 boys) with normal feet and 60 preschool children (36 girls and 24 boys) with flexible flatfoot participated in this study. The arch index (AI) was obtained from static footprints. Results: According to this study, the mean values of AI in the flatfoot and control groups showed significant difference. Conclusions: The results of this study indicated that the medial longitudinal arch development was lower in preschool children with flexible flatfoot than in the control group. This lower development was shown by higher AI. Level of Evidence: Level III.